(untitled) (Comprehensive Journal of Science, 2025)
The study addressed the problem of the decline in non – oil revenues, and their low contribution to public revenues, and to financing the state’s general budget, as they did not exceed 10% of total expenditures, which made enhancing non-oil revenues an urgent requirement to achieve financial balance and economic stability. Hence, the study aimed to demonstrate the reasons for the decline in non – oil revenues, and the impact of their reduction on the Libyan state’s general budget, relying on the descriptive analytical method and the standard method using the 10 Eviews program. The study showed that the abundance of oil revenues and the state’s reliance on them to finance its expenditures led to a decline in the importance of non-oil revenues especial taxes, and a lack of focus on economic diversification. The results of the econometric analysis showed that non-oil revenues were weak and a negative impact on the state’s general budget, while the impact of oil revenues was positive on the state’s general budget. That is, every time oil revenues increased by one unit, this led to a 24% increase in the general budget balance. The study recommended the need to strengthen the state’s public financial management and work to exploit oil revenues to expand investment in infrastructure to drive growth in non-oil sectors and benefit from the experiences of countries that have succeeded in this field, the study also included another set of findings and recommendations